Bridging the Service Divide Through Digitally Enabled Service Innovations: Evidence from Indian Healthcare Service Providers1 - Srivastava, Shirish C.; Shainesh, G. (MIS Quarterly, 2015)
The digital divide is usually conceptualized through goods-dominant logic, where bridging the divide entails providing digital goods to disadvantaged segments of the population. This is expected to enhance their digital capabilities and thus to have a positive influence on the digital outcomes (or services) experienced. In contrast, this study is anchored in an alternative service-dominant logic and posits that viewing the divide from a service perspective might be better suited to the context of developing countries, where there is a huge divide across societal segments in accessing basic services such as healthcare and education. This research views the prevailing differences in the level of services consumed by different population segments (service divide) as the key issue to be addressed by innovative digital tools in developing countries. The study posits that information and communication technologies (ICTs) can be leveraged to bridge the service divide to enhance the capabilities of service-disadvantaged segments of society. But such service delivery requires an innovative assembly of ICT as well as non-ICT resources. Building on concepts from service-dominant logic and service science, this paper aims to understand how such service innovation efforts can be orchestrated. Specifically, adopting a process view, two Indian enterprises that have developed sustainable telemedicine healthcare service delivery models for the rural population in India are examined. The study traces the configurations of three interactional resources—knowledge, technology, and institutions—through which value-creating user-centric objectives of increasing geographical access and reducing cost are achieved. The theoretical contributions are largely associated with unearthing and understanding how the three interactional resources were orchestrated for service-centric value creation in different combinative patterns as resource exploitation, resource combination, and value reinforcement. The analysis also reveals the three distinct stages of service innovation evolution (idea and launch, infancy and early growth, and late growth and expansion), with a distinct shift in the dominant resource for each stage. Through an inductive process, the study also identifies four key enablers for successfully implementing these ICT-enabled service innovations: obsessive customer empathy, belief in the transformational power of ICT, continuous recursive learning, and efficient network orchestration.